The impact of seasonal calving systems with varying pasture allowance on Cheddar cheese composition, nutritional quality, and ripening characteristics - Mark Timlin; André Brodkorb; Niamh Harbourne; Tom F. O'Callaghan; Gaetan Drouin; Sara Pacheco-Pappenheim; Deirdre Hennessy; Michael O'Donovan; Karina M. Pierce; Bernard M. Corrigan; John P. Murphy; Dmitri Pismennõi; et al. (Journal of Dairy Science, 2024)
ABSTRACT: The objective of this study was to examine the effect of stage of lactation (early, mid, and late) and proportion of pasture in the cow's diet (high: GRS, medium: PMR, and no: TMR) on the composition and quality of Cheddar cheese. Triplicate trials were carried out in each stage of lactation, and milk protein and fat contents were standardized for Cheddar cheese manufacture at pilot scale. Because cheese milks were standardized for milk fat and protein contents, gross composition did not differ as a result of diet. Fatty acid profiles of GRS cheese were significantly different from TMR, while PMR profiles were less distinct and more similar to both GRS and TMR profiles, as illustrated by partial least squares discriminatory analysis. Fatty acids including CLA C18:2 cis-9,trans-11, C22:1 n-9, and C18:3 n-3 were most influential in this separation of profiles. Fatty acid profiling revealed that GRS-derived cheese contained higher proportions of nutrients considered beneficial for human health including higher proportions of unsaturated fatty acids and omega-3 fatty acids. A biomarker model utilizing the proportions of 5 fatty acids was constructed and was effective at distinguishing between cheese of GRS, TMR, and PMR feeding systems. Proportions of ρ-κ-CN, αs2-CN and αs1-CN in cheese also differed among diets while proportions of ρ-κ-CN, αs1-CN, and β-CN were lowest in late lactation cheese. The effect of diet was less influential compared with that of stage of lactation on the ripening characteristics of cheese. An index of primary proteolysis was highest in late lactation cheese. The peptides derived from the proteolysis of κ-CN and β-CN and levels of secondary proteolysis, in particular, the proportions of 12 free AA were most influenced by stage of lactation. Overall this study demonstrated the effects of increasing pasture allowance and wstage of lactation on the nutritional quality and ripening properties of Cheddar cheese.